Internalisasi Pendidikan Berbasis karakter Aswaja an-Nahdliyah pada Siswa Madrasah Ibtidaiyah Dasussalam Kolomayang Wonodadi Blitar - Muttaqin, Asyharul; Mahsun, Toha; Mubarok, Mohammad Syahrul; Ansori, M.Subhan (Universitas Nahdlatul Ulama Blitar, 2024)
The aim of this research is to instill attitudes in students at Madrasah Ibtidaiyah (MI) Darussalam Kolomayan, Wonodadi, Blitar that reflect the values ​​of Aswaja an-Nahdliyah, in making friends, accepting and implementing rules, morals in the family and at school. The researcher's research stages used qualitative research with a case study approach. Data collection was carried out through in-depth interviews, observation and document analysis. that the values ​​of Aswaja An-Nahdliyah, especially tolerance, balance, justice and moderation, have been well internalized by MI Darussalam Kolomayang students. This internalization does not only occur through classroom learning but also through various supporting activities such as discussions, games, and role models provided by the teacher. These values ​​are able to shape students' character who is moderate, respects differences, and upholds justice. Students show a fairly high level of appreciation for these values, which are important in forming positive character in accordance with the principles of Aswaja teachings